(untitled) (REVISTA NODO, 2007)
The scale model—despite the current extensive use of digital technologies—is still the three-dimensional system of representation most required to students in Colombian architecture schools; however, its solely modern conception (white, clean, pure, ideal) stands in opposition to the widely taught theory that promotes the consideration of place, context, tradition and local technology in design, all of them without a doubt colorful, picturesque, poetic and non-industrialized. The article proposes a meditation on how this paradox contradicts the purpose of model-making itself during the formation years and, at the same time, why it leaves the materialization of the object in practical life to the employment of a dexterity that was never learned in school.